Investigating the Mechanism of Arsenic-induced Ferroptosis in the Skin - Koushki, Mehdi; Amiri-Dashatan, Nasrin; Rezaei, Mitra; Montazer, Fatemeh; Nikzamir, Abdolrahim; Vafaee, Reza; Mansouri, Vahid; Farahani, Masoumeh (International Journal of Medical Toxicology and Forensic Medicine, 2023)
Background: Ferroptosis, an oxidative and iron-dependent cell death, is a new type of regulated cell death. There are few studies on the mechanisms of ferroptosis in the skin and related diseases. Arsenic is shown to induce ferroptosis cell death. This study aimed to decipher the relationship between arsenic exposure and ferroptosis cell death in the skin. Methods: Arsenic-gene interactions were obtained. Then, skin-specific arsenic-gene interactions were screened. Ferroptosis-related genes were identified. Analysis of functional and biological interactions was performed to identify possible mechanisms. Results: The arsenic-gene interactions and the ferroptosis-related genes showed an overlap of 59 genes. Functional enrichment, protein-protein interaction, and transcription factor (TF)/miRNA target gene interaction analyses were used to look into the mechanism of arsenic-induced ferroptosis in the skin. ACTB, CTNNB1, HSPA8, SRC, RACK1, CD44, and SQSTM1 were identified as key proteins. Gene ontology analysis of these proteins indicated the mitochondrial morphology and functionality changes following arsenic-induced ferroptosis in the skin. HIF1A and SP1 TFs regulate a large number of genes compared to other TFs. Ten miRNAs with high interaction with ferroptosis-associated genes were identified. Conclusion: This work investigated the mechanism of arsenic-induced ferroptosis in the skin and identified key genes and regulators, and functional analysis highlighted the role of mitochondria in this skin exposure.